Identification of Learning Outcomes for Natural and Social Sciences Subjects on Plant Body Parts for Elementary School Students - Iksan, Muhamad (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2024)
Identification of learning outcomes of Natural and Social Sciences  subjects on the material "Parts of Plants" aims to understand the extent to which students can recognize the structure and function of plant parts. The purpose of the study was to determine the identification of learning outcomes of Natural and Social Sciences subjects on the material of Parts of Plants in Elementary School Students. This type of research uses a qualitative approach with a descriptive method to identify student learning outcomes in Natural and Social Sciences subjects, especially on the material "Parts of Plants." Data were collected through observation, interviews with teachers, and analysis of student worksheets. The results showed that most students understand the basic concepts of the function and parts of plants such as roots, stems, leaves, flowers, fruits, and seeds. However, there are some students who have difficulty in linking the function of each part of the plant with the overall life process. The results showed that learning about plant parts in grade IV of Elementary School 1 Kaobula was effective with most students understanding the basic concepts, although some had difficulty in the abstract aspects. The use of visual media, direct practice, and discussion succeeded in increasing student understanding and engagement. Various student learning styles are accommodated through a varied approach, which increases motivation and overall learning outcomes.